Acurácia dos indicadores clínicos do diagnóstico de enfermagem hipotermia em pacientes cardiopatas - Olímpio, Jéssica de Araújo (2019)
This study aims to elucidate the concept of hypothermia and to evaluate the accuracy of the nursing diagnosis Hypothermia in patients with heart disease. This is a cross-sectional study with a quantitative approach, conducted in two stages: Concept analysis of hypothermia and analysis of the accuracy of the clinical indicators of nursing diagnosis Hypothermia in patients with heart disease. The first step proposes to clarify the concept of hypothermia, its attributes, antecedents, consequent and empirical referentials, based on the model proposed by Walker & Avant (2011). In order to search the literature, an integrative literature review was carried out to obtain a sample of 66 articles, identified from the following search engines and databases: Cochrane, Lilacs, Scielo, Web of Science, Scopus, Pubmed and Google Scholar, accessed by middle of the periodical directory of the Coordination of Improvement of Higher Level Personnel. In addition to the material selected through the databases, previous reading articles obtained from reverse search were used. The second step proposes to analyze the accuracy of the clinical indicators of the nursing diagnosis Hypothermia in patients with heart disease and to verify the prevalence of this diagnosis in the presence of its clinical indicators based on the Latent Class Analysis method. The data collection was performed by means of an instrument containing sociodemographic, clinical information, and evaluation of the clinical indicators of the nursing diagnosis. Hypothermia through physical examination and collection of information in the medical records of the patients admitted to the cardiology unit. The study had a sample of 120 patients selected from the following eligibility criteria: be 18 years of age or older and hospitalized in clinical or pre-surgical treatment. The study was approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte, in compliance with Resolution no. 466/2012 of the National Health Council of the Ministry of Health and obtained a favorable opinion from the CEP under number 2,574,889 and CAAE 85607418.3.0000.5537. From the review the continent with the highest production of articles was the American (54.5%), most of the researches were produced in the last five years (43.7%), and English (97%). Regarding the concept analysis, the main attribute was the reduction of the central body temperature to less than 36 ° C. As antecedent are all the factors that influence in the reduction of the corporal temperature like the metabolic ones and the exposure to the cold. Among the consequent are: cardiac events, respiratory events, increased susceptibility to infections, tremors, hypoglycemia, increase in metabolic rate, peripheral vasoconstriction, piloerection and cold skin to the touch. The sociodemographic characterization of the patients who participated in the second stage of this study identified: a majority male (62.5%), companion (74.2%), born and resident in the state of Rio Grande of the North (65% and 59.2%), retired (59.2%), practicing religion (87.5%) and mean age was 59.7 years. Among the hospitalization reasons identified, congestive heart failure occurred with a higher prevalence (30%). Regarding latent class analysis, the prevalence for the diagnosis of nursing hypothermia in patients with heart disease was 98.33%. The clinical indicators considered sensitive, whose presence indicates the presence of the diagnosis were: reduction in glucose level, hypertension hypoglycemia, piloerection, tachycardia and cold skin to the touch; and the specific indicators, whose presence indicates the presence of the diagnosis, were: reduction of glucose level, hypoglycemia and hypertension. The latter, therefore, are good indicators to confirm the presence of the diagnosis. Concomitant reduction in the level of glucose and hypoglycemia present high values of specificity and sensitivity and are thus useful in inferring and confirming the presence of the diagnosis of hypothermia nursing in patients with heart disease.